Kunjungan Antenatal dan Kejadian Stunting di Wilayah Puskesmas Payung Rejo, Lampung - Puspitarini, Zenni; Ayu, Riska Nur Suci; Suja, Monica Dara Delia (FORIKES, 2024)
Stunting in school children is a manifestation of stunting in toddlers who experience failure to grow during the golden period, lack of nutrients for a long time and infectious diseases. Stunting is a condition of failure to grow in children resulting from chronic malnutrition so that the child is too short for his age. The aim of this study was to analyze the correlation between antenatal care visits and the incidence of stunting at the Payung Rejo Community Health Center, Central Lampung. This study used a cross-sectional design. The research subjects were 57 toddlers aged 1 to 60 months. Antenatal care visits were measured by filling out questionnaires, while the incidence of stunting was measured by anthropometry. Data were analyzed using the Chi-square test. The analysis results showed that the p-value was 0.293. Furthermore, it was concluded that antenatal care visits were not correlated with the incidence of stunting at the Payung Rejo Community Health Center, Central Lampung.Keywords: antenatal care; stunting; toddler ABSTRAK Stunting pada anak sekolah merupakan manifestasi dari stunting masa balita yang mengalami kegagalan dalam pertumbuhan pada golden periode, kekurangan zat gizi dalam waktu yang lama dan penyakit infeksi. Stunting adalah kondisi gagal tumbuh pada anak akibat dari kekurangan gizi kronis sehingga anak terlalu pendek untuk usianya. Tujuan dari penelitian ini adalah untuk menganalisis korelasi antara kunjungan antenatal care dengan kejadian stunting di Puskesmas Payung Rejo, Lampung Tengah. Penelitian ini menggunakan desain cross-sectional. Subyek penelitian adalah 57 balita yang berusia 1 sampai 60 bulan. Kunjungan antenatal care diukur melalui pengisian kuesioner, sedangkan kejadian stunting diukur dengan antropometri. Data dianalisis dengan uji Chi-square. Hasil analisis menunjukkan bahwa nilai p adalah 0,293. Selanjutnya disimpulkan bahwa kunjungan antenatal care tak berkorelasi dengan kejadian stunting di Puskesmas Payung Rejo, Lampung Tengah.Kata kunci: antenatal care; stunting; balita